Stale seedbed technique for weed control negatively impacts the indigenous AM fungal population*. Issue 3 (3rd July 2018) - Douds, David D.; Lee, Joe; McKeever, Lindsay; Duffield, Ross; Ziegler-Ulsh, Christine; Moyer, Jeff
Abstract: Among weed control tools available to organic farmers are a variety of stale seedbed techniques. Stale seedbed methods create a surface layer of soil depleted in viable weed seeds through repetitive cycles of seed germination followed by cultivation to uproot and kill those seedlings. Two experiments were conducted to examine the impact of two stale seedbed techniques, roto-tilling and spading (each at two frequencies), upon the native AM fungal communities in organically farmed high P soils. Weed biomass, propagule densities of the indigenous AM fungal communities, development of mycorrhizas in roots of transplanted leek ( Allium porrum L.) seedlings, and impact of AM fungus inoculation upon growth and yield were measured for repetitively cultivated vs. control planting beds. Stale seedbed treatments had significant negative impact upon total weed biomass the first month after planting the leek seedlings. Control beds, cultivated only just before planting, had significantly greater AM fungus propagule density than soils roto-tilled ( Pr > F = 0.0004) or spaded ( Pr > F = 0.0008) at 2–4 week intervals. Early season development of mycorrhizas in transplanted seedlings was greater in the control beds than in repetitively cultivated beds, e.g. 6% vs. 1% of root length colonized ( Pr > F = 0.0001) two weeks after transplanting in Exp II. Even though the stale seedbed techniques had negative impacts upon the indigenous AM fungal populations, there was no measurable impact on crop yield in the high P soils used here. Nevertheless, farmers may want to consider use of AM fungus inoculation of vegetable seedlings transplanted into stale seedbed-treated fields low in plant available P.